Performance comparison of different Java versions - Mateusz, Maciasz (Journal of Computer Sciences Institute, 2017)
This article describes the performance results of two versions of Java - 1.7 and 1.8. Three applications were created for this purpose. The first one is responsible for preparing the test data. Two more implement performance tests depending on the virtual machine version of Java. The methods in the test applications were designed to analyze the performance of collections and the rate of change of the variables by two threads.